Las relaciones comerciales marítimas entre Andalucía occidental y el Mediterráneo central en el II milenio a.C - De Caso Bernal, Mercedes, (Access archaeology., 2020)
This volume reflects on the unique status of the Western Mediterranean in the Bronze Age, considering the independence of its development and the existence of an indigenous maritime trade. It looks at ways to establish a chronology of the period that is not based solely on ceramic typologies, and aims to clarify the cultural exclusion to which the Lower Guadalquivir is subjected.